SHAKESPEARE’S TRAGEDY OF MACBETH AS A STRANGE ATTRACTOR FOR THEATER PERFORMANCES AND CINEMATIC ADAPTATIONS - Soenarto, Iswahyudi; Wibawarta, Bambang (UI Scholars Hub, 2023)
Chaos theory explicates how small things can result in big differences. Its basic principles can provide an alternative means for literary and non-literary interpretations. This study will explore how the principles of chaos theory can be utilized, together with commonly used literary theories, as an analytic lens to analyze the dramatic text of Shakespeare. The argument is built upon how Macbeth, viewed as a complex and chaotic system, become a strange attractor for both theater performances and cinematic adaptations, in an effort to understand the interconnection between the play and its reproductions as complex networks. Various elements of the text will be discussed, including its structure, language expressions and character patterning, as well as the choices of action – reaction determined to be taken by the characters in the play.